Manajemen Pendidikan Anak Usia Dini (PAUD) Dalam Rangka Meningkatkan Mutu Pembelajaran Pada Anak - Utari, Rezie Zilvia; Alimni, Alimni (Early Childhood Research and Practice, 2024)
Education in Indonesia, especially PAUD education, is of great concern to the government. Early childhood education includes support that stimulates children's development and growth. This educational process is often called the golden age, namely the period of growth and development of children when the child's mind and body are at their maximum condition. This research aims to understand how the Rahayu PAUD management model can be used to improve the quality of early childhood education. This research method uses qualitative methods with descriptive methods, data collection uses observation, interview and recording techniques. Based on the results of data analysis of Rahayu PAUD preschool education facilities, it can be said that this preschool education facility has an effective and efficient level of management because it can maximize existing human resources. The implementation of PAUD management is carried out optimally to meet national education standards in accordance with the provisions of laws and government regulations.